Conhecimento dos acadêmicos de enfermagem sobre segurança do paciente (Research, Society and Development, 2021)
Objective: To analyze the knowledge of nursing students on Patient Safety. Methodology: This is a descriptive research, with a quantitative approach, carried out with 51 students of the Bachelor of Nursing course at a private higher education institution, located in the city of Teresina, Piauí. Data collection was carried out in November 2018 after authorization by the Research Ethics Committee under opinion number 3,011,689. Results and discussion: It was found that most of the students were female, with an average age of 22 years old and single marital status. It was also found that the majority of students involved in the research had a class on patient safety, know the term patient safety and adverse events and seek to promote patient safety. However, the minority knew the six goals that are part of safe care, as well as the ten steps of patient safety and the Patient Safety Center. Conclusion: Thus, it is believed that this study will provide professional nurses with knowledge about patient safety, skills and attitudes, in order to improve the quality and safety of health care in the country and to awaken the interest of educators and students for this question.